Propagation-based phase-contrast tomography of a Guinea pig inner ear with cochlear implant using a model-based iterative reconstruction algorithm - Hehn, Lorenz; Gradl, Regine; Voss, Andrej; Guenther, Benedikt; Dierolf, Martin; Jud, Christoph; Willer, Konstantin; Allner, Sebastian; Hammel, Joerg U.; Hessler, Roland; Morgan, Kaye S.; Herzen, Julia; et al. (Biomedical Optics Express, 2018)
Propagation-based phase-contrast computed tomography has become a valuable tool for visualization of three-dimensional biological samples, due to its high contrast between materials with similar attenuation properties. However, one of the most-widely used phase-retrieval algorithms imposes a homogeneity assumption onto the sample, which leads to artifacts for numerous applications where this assumption is violated. Prominent examples are biological samples with highly-absorbing implants. Using synchrotron radiation, we demonstrate by the example of a guinea pig inner ear with a cochlear implant electrode, how a recently developed model-based iterative algorithm for propagation-based phase-contrast computed tomography yields distinct benefits for such a task. We find that the model-based approach improves the overall image quality, removes the detrimental influence of the implant and accurately visualizes the cochlea.
CRIS-Team Scopus Importer:2023-03-08